PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V-A UPT SD NEGERI 060921 MEDAN SUNGGAL - Liana Siburian; Salma Tampubolon; Wisni Handayani Gulo; Indah Meylissya Manalu; Felis Clausia Parhusip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve Indonesian language learning outcomes in the material of determining the main idea of a paragraph through the application of the Think Pair Share (TPS) cooperative learning model for class V-A students of UPT SD Negeri 060921 Medan Sunggal. The background of this study is the low student learning outcomes, where there are still 10-15 students who have not reached the Minimum Completion Criteria (KKM) and have difficulty in determining the main idea of a paragraph. This study uses the Classroom Action Research (CAR) method of the Kemmis and McTaggart model which is carried out in two cycles, namely planning, action implementation, observation, and reflection. The research subjects were 23 class V-A students. Data collection techniques used learning outcome tests, observation, and documentation. The results of the study indicate that the application of the Think Pair Share (TPS) learning model is able to improve student learning outcomes. In Cycle I, 13 students (56.52%) achieved learning completion with an average score of 57. After improvements were made in Cycle II, the number of students who completed the learning increased to 18 students (78.26%) with an average score of 77. In addition, teacher activity increased from 60.5% to 79.5%, while student activity increased from 60 to 86. Thus, it can be concluded that the implementation of the Think Pair Share (TPS) cooperative learning model is effective in improving Indonesian language learning outcomes in the material on determining the main idea of paragraphs for class V-A students at UPT SD Negeri 060921 Medan Sunggal.